Cyclotron production of no carrier added 186gRe radionuclide for theranostic applications - Khandaker, Mayeen Uddin *; Nagatsu, K.; Minegishi, K.; Zhang, M. R.; Jalilian, A. R.; Bradley, D..A. (Elsevier, 2020)
186gRe (T1/2 = 3.7183 d, E(β−)mean = 346.7 keV, I(β−)mean = 92.59%), a mixed beta and γ-emitter shows great potential for use in theranostic applications. The dominant 185Re(n,γ) route, via use of a nuclear reactor, provides 186gRe in carrier added form with low specific activity, while cyclotrons offer no carrier-added (NCA) high specific activity production of 186gRe. However, to be able to select the best possible nuclear reaction and to optimize the production route via the use of a cyclotron, information on the excitation function for the reaction of interest as well as for the competing reactions is necessary. Accordingly, we have conducted a detailed study of the excitation functions for natW(d, x) reactions in seeking optimized parameters for the NCA production of 186gRe. Noting a discrepancy among the experimental data, we made an evaluation of the available literature, finally selecting optimum parameters for the production of 186gRe via the 186W(d,2n)186Re reaction. These beam parameters were then used for batch production of 186gRe by irradiating an enriched 186W metallic powder target, followed by a subsequent automated chemical separation process. The preliminary results show 98.1% radionuclidic purity of 186gRe at 8 h subsequent to the End of Bombardment (EOB), offering the potential for use in clinical applications.